Fundamentals of micro-particle removal by liquid oxide - Sharma, Mukesh (My University, 2019)
The grades of steel used for automotive bodies are interstitial free steel grades and titanium stabilized ultra-low carbon steel grades. During the manufacturing of these grades, the addition of titanium in liquid steel is achieved in the steel refining units and may cause processing problems. Titanium reacts with the dissolved aluminum and oxygen to form complex solid aluminum titanate type micro-particles (inclusions). During the flow of titanium alloyed steel grades containing solid inclusions (such as aluminum titanate and alumina type inclusions), the clog accompanied by steel skull can be formed at the submerged entry nozzle between the tundish and the mold. To reduce the effects of aluminum titanate type inclusions, they can be either modified or removed. The current study focused on the removal of Al2O3, TiO2, and Al2TiO5 inclusions by dissolving them in slag in the temperature range of 1430 – 1600 °C using a high-temperature confocal scanning laser microscope. In this technique, a single particle (inclusion) is placed on the surface of a solid slag, and the inclusion-slag system is heated to steelmaking temperatures. The dynamic changes in inclusion size are measured to determine dissolution kinetics and mechanism. This work has developed a complex oxide particle synthesis technique and provides the first-ever kinetic data for removal of aluminum titanate inclusions into steelmaking slags. It is found that Al2O3 inclusions have a slower dissolution rate than that of Al2TiO5 inclusions followed by TiO2 inclusions. The rate-controlling steps are investigated using a shrinking core model. It is shown that the rate-controlling step for dissolution of both Al2O3 and Al2TiO5 inclusion types is the mass transfer of alumina. Evidence in support of this finding is the particle-slag interface characterization by line scan analysis and calculated diffusivity values being inversely proportional to the viscosity of slag. The dissolution path of aluminum titanate is proposed in the following steps. First, aluminum titanate dissociates into alumina, titanium oxide and oxygen while slag penetrates through the particle. In the next step, the alumina and titanium oxide dissolves in slag, and the oxygen leaves the system. The existence of gas bubbles enhances the overall rate of Al2TiO5 dissolution. The current work establishes a detailed understanding of the dissolution of Al-Ti-O type inclusions in steelmaking slags. This knowledge will inform steelmakers on which inclusions of different chemistry can be removed preferably and develop strategies on better slag design to produce superior quality steel with reduced operational downtime.
Keywords: dissolution mechanism, aluminium titanate inclusion, confocal scanning laser microscope, mass transfer control